Strategies and Challenges of Development Economy in Realizing Sharia-Based Sustainable Growth - Huda, Syamsul; Yuliati, Anik (Institut Manajemen Wiyata Indonesia, 2025)
Islamic economics plays a crucial role in addressing the economic challenges of sustainable development in Indonesia. With principles based on social justice, wise management of natural resources, and redistribution of wealth, usury is prohibited. This research aims to examine the role of Islamic economics principles and identify appropriate strategies to overcome the economic challenges of sustainable development in Indonesia. This research employs a qualitative approach, utilizing a systematic review method to analyze the latest scientific articles from the past decade, as well as e-books. The results showed that the principles of the five central values of Islamic economics, such as tawhid, justice, prophethood, khilafah, and ma'ad, can contribute to sustainable economic development. Islamic economic strategy in Indonesia plays a crucial role in promoting sustainable economic growth by increasing public awareness of Islamic economic literacy, strengthening the Islamic financial sector, developing the halal industry, leveraging digital technology, and fostering collaboration between the government and society to achieve inclusive welfare. This study concludes that by applying the principles of sharia economics, Indonesia can create a fairer financial system, reduce social inequality, and ensure long-term economic stability. The goal of this research is to create a fair, inclusive, and sustainable economic system that enhances people's welfare and preserves the environment by applying Sharia principles in all aspects of economic development.